0367 Lemborexant Treatment for Insomnia: 6-month Safety. (12th April 2019) - Kärppä, Mikko; Moline, Margaret; Yardley, Jane; Pinner, Kate; Perdomo, Carlos; Filippov, Gleb; Zammit, Gary
Abstract: Introduction: There is an unmet medical need for effective, well-tolerated pharmacological treatments for insomnia disorder that are studied over the long-term. Safety results are presented from the placebo-controlled first 6 months of a 12-month Phase 3 study of lemborexant (LEM), a dual orexin receptor antagonist under development for treatment of insomnia. Methods: SUNRISE-2 was a Phase 3, 12-month global study in female and male adults with insomnia disorder that included a 6-month double-blind, placebo (PBO)-controlled treatment period followed by a 6-month blinded active treatment period. Subjects were randomized to PBO, LEM 5mg (LEM5) or LEM 10mg (LEM10) for the 1 st 6 months. Results: 959 subjects were randomized and treated: 321 (PBO), 319 (LEM5), and 319 (LEM10). Most completed 6 months of treatment: 80.1%, 78.7% and 70.8%, on PBO, LEM5 and LEM10, respectively. Treatment-emergent adverse events (TEAEs) were reported for 62.7%, 61.1% and 59.6% of subjects on PBO, LEM5 and LEM10, respectively. Most were mild or moderate, with severe TEAEs in 3.1% (PBO), 4.1% (LEM5) and 2.5% (LEM10) of subjects. Overall, 3.8% (PBO), 4.1% (LEM5) and 8.3% (LEM10) of subjects discontinued study drug for TEAEs. TEAEs reported for ≥3% and >PBO in either LEM group were, for PBO, LEM5 and LEM10 respectively: somnolence (1.6%, 8.6%, 13.1%), headache (6.6%, 8.9%, 6.7%), influenza (4.7%, 4.8%, 5.1%), upper respiratory tract infection (3.1%, 4.1%, 3.5%), fatigue (0.3%, 3.8%, 3.5%), and back pain (2.5%, 3.8%, 2.9%). Treatment-emergent serious adverse events (SAEs) were reported by 1.6% (PBO), 2.2% (LEM5) and 2.9% (LEM10) of subjects. Most SAEs were reported in only one subject in any group. There were no deaths or clinically significant findings for laboratory tests, vital signs, weight or electrocardiograms. There were no clinically relevant differences in the safety profiles across age groups, sex, race, region, or body mass index (BMI). Conclusion: Lemborexant was generally well tolerated for up to 6 months treatment. Support (If Any): Eisai, Inc., Purdue Pharma L.P.